Innovative model of educational organization - Сошко, Александр Иванович; Сошко, Наталья Николаевна (Eastern-European Journal of Enterprise Technologies, 2011)
Offered some guidelines on the possible solution to enhance its effectiveness. The most important ones are: continuing education, fundamentalization maintenance of discipline, the complexity of the fundamental categories of discipline and built-in (additional) education curriculum of foreign universities